2003
DOI: 10.1002/bit.10656
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium tolerance and antioxidative defenses in hairy roots of the cadmium hyperaccumulator, Thlaspi caerulescens

Abstract: Plant species capable of hyperaccumulating heavy metals are of considerable interest for phytoremediation and phytomining. This work aims to identify the role of antioxidative metabolism in heavy metal tolerance in the Cd hyperaccumulator, Thlaspi caerulescens. Hairy roots of T. caerulescens and the non-hyperaccumulator, Nicotiana tabacum (tobacco), were used to test the effects of high Cd environments. In the absence of Cd, endogenous activities of catalase were two to three orders of magnitude higher in T. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
1
9

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(95 citation statements)
references
References 52 publications
7
78
1
9
Order By: Relevance
“…In the particular case of Thlaspi caerulescens the analysis of root cell wall fractions revealed that the hairy roots partitioned virtually all the Cd uptake by the biomass in the cell wall fraction for 7 to 10 days before allowing passage into the symplast (Nedelkoska and Doran, 2000). The mechanism of Cd hyperaccumualtion in this species seems to be related to an efficient antioxidative defense, particularly an enhanced catalase activity (Boominathan and Doran, 2003). Further studies will be required to define the specific mechanisms of tolerance to Pb, Cr and Mn in S. americanus root cultures.…”
Section: Discussionmentioning
confidence: 91%
“…In the particular case of Thlaspi caerulescens the analysis of root cell wall fractions revealed that the hairy roots partitioned virtually all the Cd uptake by the biomass in the cell wall fraction for 7 to 10 days before allowing passage into the symplast (Nedelkoska and Doran, 2000). The mechanism of Cd hyperaccumualtion in this species seems to be related to an efficient antioxidative defense, particularly an enhanced catalase activity (Boominathan and Doran, 2003). Further studies will be required to define the specific mechanisms of tolerance to Pb, Cr and Mn in S. americanus root cultures.…”
Section: Discussionmentioning
confidence: 91%
“…According to Chaignon and Hinsinger (2003), higher concentrations of copper can inhibit root growth before shoot growth and can accumulate in the roots without any significant increase in its content of the aerial parts. Previous studies have demonstrated that growth of T. caerulescens roots was essentially unaffected by 20 ppm concentration of cadmium relative to the control cultures without cadmium (Boominathan and Doran, 2003). Root density and the depth of rooting are particularly significant in the context of phytoremediation.…”
Section: Effect Of Heavy Metals On Root Growthmentioning
confidence: 99%
“…Higher Cd concentrations are generally observed in plants grown on soil subjected to the metal-processing industry, sludge application, and long-term fertilization, with up to 70 mg Cd kg -1 DM in lettuce (Gerard et al, 2000). Moreover, many studies have demonstrated that Cd taken up by plants accumulates at higher concentrations in the roots than in the leaves (Boominathan and Doran, 2003). Alloway (1995) reported that Alyssum species which are naturally adapted to serpentine soils can accumulate over 2% Ni.…”
Section: Heavy Metal Uptake By Plant Tissuementioning
confidence: 99%
“…In plant cells, cadmium tends to be stored in the apoplast and in vacuoles, which may contribute to Cd tolerance in hyperaccumulator plants and common crops (Boominathan and Doran, 2003;Ma et al, 2005;Liu et al, 2007). Cadmium may cause growth inhibition related to reduction of mitotic activity, induction of chromosome aberrations, toxicity to nucleoli in apical meristems (Liu et al, 2003(Liu et al, /2004Zhang et al, 2009;Qin et al, 2010), damage of macromolecules, mainly proteins and lipids (Skórzyńska-Polit and Krupa, 2006) and DNA (Li et al, 2005), and disturbance of the organization of the microtubular cytoskeleton in interphase and mitotic cells Liu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%